The European Union in Africa: the linkage between security, governance and development from an institutional perspective - (:unkn) unknown (My University, 2009)
The international community currently favours an approach to development that stresses a triangular linkage between security, good governance and economic development. This approach clearly informs the European Union's agenda in Africa, which has progressively integrated governance and security elements. This paper will show that this agenda is at least as much determined by the bureaucratic and national affiliations of the concerned EU actors as it is by African realities and international trends. African security indeed triggers a competition between the different European institutions, eager to be the driving force for a policy that can offer some additional resources and autonomy. The consistency and the credibility of the EU security policy in Africa will therefore depend on the responses provided to these institutional rivalries.
Keywords: African Research